Monologue patterns among primary school teachers in Nigeria (2005)
In this study, a classroom interaction sheet was used to find out the proportion of teaching/ learning time the teacher spends talking non-stop (monologue). In the cases analyzed, an average of 4.25% of the teaching /learning time in social studies lessons of primary six was found to be the minimum time spent on monologue while as much as 26% of the teaching-learning time was recorded as average time for primary science in primary six. The samples used for the study cut across the six geo-political zones of Nigeria.